DINAMIKA SOSIAL, EKONOMI, DAN LINGKUNGAN AKIBAT PEMBANGUNAN INDUSTRI PADAT KARYA DI KABUPATEN JEPARA - Ratnawati Yuni Suryandari; Ken Martina Kasikoen; Elsa Martini; Fachmi Tamsil (Media Bina Ilmiah, 2025)
Industrial development is closely linked to regional growth. Since 2014, Jepara Regency has experienced significant growth in labor-intensive industries. This expansion has been driven by the availability of vast land and relatively lower minimum wages compared to other regions in Banten and West Java Provinces, attracting foreign investors to the area. This investment growth is evident from the emergence of various labor-intensive industries in Batealit, Pecangaan, and Mayong Districts. This study aims to analyze the social, economic, and environmental impacts of labor-intensive industry development in Jepara Regency. Data were collected through questionnaires measuring the industry's effects on the community using the Likert scale method and quantitative descriptive analysis. The research employed random sampling with 100 respondents from Mayong and Pecangaan Districts, conducted over six months, from July to December 2023. The industrial sector has led to changes in lifestyle and social values, increased income and community welfare, and environmental pollution, including air, water, and soil contamination due to industrial waste. Therefore, while labor-intensive industries contribute to economic benefits, proper management is essential to mitigate negative impacts and maximize benefits for both the community and the environment.